Application Of The Classroom Coexistence Program "Let's Be Friends" For Social Skills In Ecuadorian Adolescents - Santos Vera, Patricia Yolanda (2024)
In adolescence there are a series of physical, psychological and social challenges, this stage is the beginning of adulthood so that coexistence with others helps the constitution of the personality, in this sense the objective was to determine the influence of the classroom coexistence program "Let's be friends" in the improvement of social skills in Ecuadorian adolescents, the results determine that the experimental group presented higher values compared to the control group in the post test situation for social skills, also the p value between groups is 0.009 < 0.05. The application of the program was effective, so the application of further research oriented to psychological intervention specifically in social skills training, expression of emotions and relationship with adults is discussed.